Lithium lanthanum titanate perovskite ionic conductor: Influence of europium doping on structural and optical properties - Fernandes, Silvia Leticia [UNESP]; Gasparotto, Gisele [UNESP]; Teixeira, Guilhermina Ferreira [UNESP]; Cebim, Marco Aurélio [UNESP]; Longo, Elson; Zaghete, Maria Aparecida [UNESP] (Elsevier, 2018)
The present study reports the insertion of europium ions into the network of lithium lanthanum titanate, La0.5Li0.5TiO3, powders. The materials were prepared efficiently via the Pechini method and were characterized using thermogravimetric analyses, X-ray diffraction, high-resolution electron microscopy and photoluminescence spectroscopy. The results obtained demonstrate the high structural disorder of La0.5Li0.5TiO3 (LLTO) as well as the different environments noticed by Eu3+ ions in the La0.5Li0.5TiO3 host lattice. Our results are essentially important once they unfold a better understanding of the complex nature of La0.5Li0.5TiO3 compounds structure.
Keywords: B. Perovskite; C. Photoluminescence; D. Lithium lanthanum titanate; E. Lithium battery